2018
DOI: 10.1128/jb.00728-17
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Utilizes Host-Derived Lipoprotein Particles as Sources of Fatty Acids

Abstract: Methicillin-resistant (MRSA) is a threat to global health. Consequently, much effort has focused on the development of new antimicrobials that target novel aspects of physiology. Fatty acids are required to maintain cell viability, and bacteria synthesize fatty acids using the type II fatty acid synthesis pathway (FASII). FASII is significantly different from human fatty acid synthesis, underscoring the therapeutic potential of inhibiting this pathway. However, many Gram-positive pathogens incorporate exogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 85 publications
5
84
1
Order By: Relevance
“…We have previously shown that SCUFAs became about 25% of the total fatty acid profile of S. aureus grown in 100% total bovine serum (6). Delekta et al grew S. aureus in the presence of human LDL and analyzed the PG species produced under these conditions by mass spectrometry (13). PG species containing C16:1, C18:1, C18:2, and C20:1 were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that SCUFAs became about 25% of the total fatty acid profile of S. aureus grown in 100% total bovine serum (6). Delekta et al grew S. aureus in the presence of human LDL and analyzed the PG species produced under these conditions by mass spectrometry (13). PG species containing C16:1, C18:1, C18:2, and C20:1 were observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that S. aureus is unable to biosynthesize SCUFAs, and cells grown in the presence of serum (6), liver extract (12), and human low-density lipoprotein (LDL) and egg yolk LDL (13) have been shown to contain significant amounts of SCUFAs in their fatty acid profiles. In addition, free fatty acids are incorporated into phospholipids from medium supplemented with them (14, 15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite excellent in vitro activity, the therapeutic value of inhibitors of fatty acid synthesis as mono-therapeutic agents has attracted much debate [20,21]. Several bacteria, including S. aureus , can utilise fatty acids present in the host to generate phospholipids [21-24]. Although wild-type S. aureus strains cannot fully substitute exogenous fatty acids for endogenous fatty acids synthesised via FASII, there is evidence that some clinical isolates have acquired mutations that enable them to fully bypass endogenous fatty acid biosynthesis by utilising host-derived fatty acids [22,25,26].…”
Section: Introductionmentioning
confidence: 99%